Ultrafast Lasers in Additive Manufacturing - Saunders, Jacob (My University, 2022)
Ultrafast lasers are valuable research and manufacturing tools. The ultrashort pulse duration is comparable to electron-lattice relaxation times, yielding unique interactions with matter, particularly nonlinear absorption, melting, and ablation. The field of ultrafast laser manufacturing is rapidly evolving with advances in related laser technologies. The applications of ultrashort pulse lasers in additive manufacturing aim to fill gaps left by conventional techniques especially on the nano- and micro-scale. Concurrently, uptake of ultrafast fiber lasers for micromachining has increased, and may replace the Ti:Sapphire laser as the ultrafast laser of choice. Both additive and subtractive manufacturing are accomplished with ultrafast lasers which presents the possibility of hybrid, all-in-one devices using a single laser source. As one such combination of laser techniques, ultrashort pulse surface modification of additively manufactured metals is an area of limited investigation. This thesis aims to address the ever-changing landscape of ultrafast laser manufacturing by 1) reviewing ultrafast laser additive manufacturing techniques and recent advancements 2) comparing the design, operation, and micromachining potential of a commercial ultrafast Ti:Sapphire and ultrafast fiber laser, and 3) investigating femtosecond ablation of as-printed additively manufactured Ti-6Al-4V at a range of parameters to test the feasibility of surface feature control. Ultrafast laser additive manufacturing is still in its infancy with mostly niche applications. The ultrafast fiber laser architecture is found to deliver a platform that is easier to operate and maintain and has superior micromachining throughput relative to Ti:Sapphire lasers. In our experimental work, five main surface morphologies are obtained by femtosecond ablation of a rough Ti-6Al-4V surface: laser-induced periodic surface structures (LIPSS), undulating grooves, micro-ripples, grooves, and micro-cavities. Transitions between ablation regimes and evolutions of the surface under increasing pulse energy and number of pulses are observed. These patterns allow for control over the surface geometry without the need for post-printing polishing.
Keywords: ultrafast laser; additive manufacturing; ablation; fiber laser; Ti-6Al-4V; selective laser melting